A scoping review of workplace violence against healthcare workers in Singapore - Sing, Phoebe; Lau, Arthur Chin Haeng (Frontiers in Public Health, 2025)
IntroductionWorkplace violence (WPV) has plagued healthcare settings, endangering healthcare workers striving to prioritise patient care. This scoping review aims to explore the prevalence, characteristics, risk factors, and interventions addressing WPV in Singapore’s healthcare sector.MethodsThis scoping review employed the Arksey and O’Malley framework and the PRISMA guidelines. Systematic searches were conducted using MEDLINE, PubMed, Google Scholar, and ScienceDirect for studies published between 2003 and 2024. Grey literature and government reports were also reviewed. The inclusion criteria focused on primary studies conducted in Singapore involving healthcare workers (HCWs) as WPV victims. Data were extracted on study characteristics, prevalence, risk factors, and interventions.ResultsEight studies met the inclusion criteria, indicating a high and increasing prevalence of WPV. Verbal abuse was the most frequently reported form of abuse, followed by physical violence. Key risk factors included alcohol intoxication and patient dissatisfaction. Existing interventions, such as online reporting systems, self-defence training, and aggression management workshops, lacked standardisation and effectiveness. HCWs have proposed enhanced police protection, advanced alert systems for repeat offenders, stricter legal consequences, and public awareness campaigns.DiscussionUnder-reporting was identified to be a key factor in the persistent prevalence of WPV. The implementation of the Tripartite Framework, along with the development of a robust reporting system, could reduce instances of under-reporting, thereby providing a more accurate representation of the extent of WPV. Employing the Haddon Matrix may offer a comprehensive approach to analysing the issue and informing targeted interventions.ConclusionWPV persists in Singapore’s healthcare sector. While the Tripartite Framework is a step forward, further integration of HCW-recommended strategies is required. Future research should evaluate its impact on WPV reduction.